2013
DOI: 10.1016/j.ijid.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Rapid virological response tailors the duration of treatment in hepatitis C virus genotype 3 patients treated with pegylated interferon alfa-2a and ribavirin in Pakistan

Abstract: RVR is useful to individualize the duration of treatment and to predict the treatment outcome. A short treatment of 16 weeks is as effective as 24 weeks in HCV genotype 3 patients who achieve RVR, who have a low BMI, and are younger in age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The present study demonstrated a substantial difference in the sustained virological response rate between patients with no and significant liver fibrosis by univariate logistic analysis (79.5% vs. 48%, p = 0.003). The presence of significant liver fibrosis and cirrhosis has long been recognized to be associated with lower probability of treatment success in GT3 patients; our conclusions concerning mild liver fibrosis as a favorable factor are in agreement with those reported by many other investigators [5, 6, 15, 19, 23]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study demonstrated a substantial difference in the sustained virological response rate between patients with no and significant liver fibrosis by univariate logistic analysis (79.5% vs. 48%, p = 0.003). The presence of significant liver fibrosis and cirrhosis has long been recognized to be associated with lower probability of treatment success in GT3 patients; our conclusions concerning mild liver fibrosis as a favorable factor are in agreement with those reported by many other investigators [5, 6, 15, 19, 23]. …”
Section: Discussionsupporting
confidence: 93%
“…Several studies have supported our findings that younger patients chronically infected with GT3 are more likely to achieve an SVR during therapy with interferon and RBV [6, 13, 14, 2326]. …”
Section: Discussionsupporting
confidence: 87%
“… 14 This was higher than the response rate in a Canadian study (54%). 15 Host genetics, 15 geographic variations, 16 difference of body weight in race, 17 and pretreatment conditions among study groups may account for the difference in response status. Our findings indicated that RVR was not a significant predictor of SVR, suggesting SVR was achieved without RVR in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable rate of SVR such as ≥80% in patients infected with GT3 were reported in other settings. 16 , 22 In a serological study on HCV-infected patients in Myanmar, 75% (18/24) were with GT3. 10 A concern was that there was a comparable SVR between GT1 (81.2%) and GT3 (85.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have defined the pretreatment patient features, such as viral genotypes and subjects with favorable IL28B genotypes, markedly affect the likelihood of attaining a SVR ( 1 , 10 - 12 ). On-therapy kinetics of antiviral response also plays an important role; the rapid and early virological response are the most important factors ( 13 - 15 ). Moreover, although the relapse rate over time is one of the most important problems, which is clinicians’ concern, little is known about the effect of these values on relapse in the management of long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%